Draft Annual Plan 1976-77 Vol. I Government of Tripura - Planning Commission (Planning Commission, 1976)
The scope for expanding employment opportunities and raising the peoples level of living generally lies in achieving diversification of economic activities in the State. The pressure of population on land must be reduced by diverting a sizeable portion of the existing number of workers depending on agriculture to other sectors like Industries, Transport, Communication and other services. These are in lad inter dependent. Development of roads, road transport, railways, communication, power, irrigation facilities etc. in other words, the infrastructure of the economy is vital for improving agricultural production and developing industries. On the other hand, as the volume of agricultural and industrial output rises, trade, commerce transport and other service sectors will automatically be stimulated and expanded.
Government of Tripura, Development Department (Planning and Coordination)
Government of Tripura Development Department